Online monitoring of water pollution level based on dissolved oxygen (DO) and biochemical oxygen demand (BOD) using wireless sensor system. Issue 1 (July 2021) - Sugiharto, W H; Ghozali, M I; Suryono, S; Susanto, H; Budihardjo, M A
Abstract: In the case of water pollution, including the sea, rivers, lakes, and reservoirs, usually when measuring the parameter of Dissolved Oxygen (DO) and Biochemical Oxygen Demand (BOD) values exceeds the pollution level. Online and continuous monitoring is essential to monitor water conditions so that if there is pollution, it can be immediate handling. Wireless sensor network technology becomes part of the Internet of Things makes it possible for online data acquisition from several node stations that are spread in monitoring locations. This paper purpose the online BOD dan DO data acquisition continuously builds with combine the wireless sensor system and database replication concept. From implementing a database replication method for online monitoring of water pollution level, database replication continuously ensures consistency and prevents redundant data between node sensor station and server database, and provides reliable information on the www website.